Unintended consequences: Advice for politicians and policy analysts - Frank Milne (Queen's University, Department of Economics, 2016)
This paper is aimed at providing advice to young Australian Politicians and Policy Analysts. The paper explains common dangers in policy formulation and implementation. It also explains the usual political pressures that distort policy formulation and common sources of policy failures.
Keywords: E60; E65; 330; Economic Policy formulation and implementation; Australia